Sustainable practices for electrical energy network management: A literature review and proposal - Vieira, Gaspar Gonçalves (2015)
Many different approaches have been proposed for improving energy network management. Although these diverse contributions, most approaches for clearly identifying and accurately solving the real problems remain rather inefficient. This is greatly due to the absence of use of completely integrated and sustainable models with Organizations playing fundamental rolls through the use of effective and efficient decision support tools. One such typical problem is related to the accurate identification and the precise calculation of electrical energy losses, which still remains unsolved as well as the clear specification of the critical points and segments in the networks were problems do occur. Consequently, there is still a lack of effective prioritization of actions and interventions in order to reduce those problems. Therefore, in this paper we propose a model for sustainable energy network management were the organizational element assumes a crucial function.